2012
DOI: 10.1111/j.1365-2915.2012.01017.x
|View full text |Cite
|
Sign up to set email alerts
|

Rickettsia felis in cat fleas, Ctenocephalides felis parasitizing opossums, San Bernardino County, California

Abstract: Los Angeles and Orange Counties are known endemic areas for murine typhus in California; however, no recent reports of flea-borne rickettsioses are known from adjacent San Bernardino County. Sixty-five opossums (Didelphis virginiana) were trapped in the suburban residential and industrial zones of the southwestern part of San Bernardino County in 2007. Sixty out of 65 opossums were infested with fleas, primarily cat fleas, Ctenocephalides felis (Bouché, 1835). The flea minimum infection rate with Rickettsia fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 31 publications
1
24
1
1
Order By: Relevance
“…14,18,21,33 However, overall prevalence values that are lower 17,25 and higher 12,22 than our results for R. felis have been reported, a variation that is most likely attributable to differences in geographic and animal factors. The observation of a higher overall percentage of R. felis in C. felis than in other flea species and detection of R. felis in C. canis and P. irritans collected from dogs in our study is consistent with those of other reports.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…14,18,21,33 However, overall prevalence values that are lower 17,25 and higher 12,22 than our results for R. felis have been reported, a variation that is most likely attributable to differences in geographic and animal factors. The observation of a higher overall percentage of R. felis in C. felis than in other flea species and detection of R. felis in C. canis and P. irritans collected from dogs in our study is consistent with those of other reports.…”
Section: Discussioncontrasting
confidence: 55%
“…13 Although C. felis is considered to be the only known biological vector of R. felis, 10 R. felis has recently been detected in different flea species in many countries in Europe, [14][15][16] Asia, 17 north and sub-Saharan Africa [18][19][20] and North and Latin America. 21,22 However, in Ethiopia, few reports are available, 23 although R. felis has recently been reported in a small number of P. irritans and C. felis specimens collected from human dwellings in southwestern regions of this country. 19 Bartonella spp.…”
Section: Introductionmentioning
confidence: 99%
“…I. scapularis larvae were found on one of the dogs at the time of mite collection, thus it is also possible that both dogs were infected via tick bites. C. felis, is known to infest raccoons, opossums, foxes, coyotes, and other small mammals that inhabit the urban, suburban, and rural environments (Gracia et al 2008, Abramowicz et al 2012. Interestingly, a recent study using PCR amplification from raccoon and cat blood specimens reported B. henselae bacteremia in 32% of raccoons and 35% of feral cats on St. Simons Island, Georgia, suggesting that raccoons that comingle with cats and their fleas may serve as wildlife reservoir hosts for B. henselae (Hwang and Gottdenker 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Minimum infection rates (MIRs) were calculated as the percentage of a ratio between the total number of flea pools positive for R. felis and the total number of fleas tested. 33 We made this assessment with the assumption that only one flea from each positive pool was positive for the Rickettsia gene analyzed. A total of 123 (MIR; 9.2%) pools yielded PCR products of the expected size for gltA, 104 (7.8%) pools yielded PCR products of the expected size for ompB, and 91 (6.8%) pools yielded PCR products of the expected size for 17kD gene (Tables 1 and 2); 79 (5.9%) pools were positive for the three genes evaluated from all species with the exception of X. cheopis.…”
Section: Resultsmentioning
confidence: 99%
“…[2][3][4] However, the MIR reported here for C. felis (5.3%) is lower than MIRs reported in other countries, like Brazil (14.3%), 34 Taiwan (8.2%), 35 and the United States (13.3%). 33 We must emphasize that these rates correspond to MIRs, because they were calculated with the assumption that only one flea from each positive pool was positive for the Rickettsia gene analyzed; therefore, positive pools were not further corroborated to obtain the results for individual fleas, because we had limited resources.…”
Section: Discussionmentioning
confidence: 99%